[tex]f(x) = 2x^2 - 3x + 1 = 0[/tex]

ajuda urgente manos por favor


Resposta :

Resposta:

Explicação passo a passo:

Resposta:

S={1, 1/2}

Explicação passo-a-passo:

[tex]f(x) = 2x {}^{2} - 3x + 1[/tex]

[tex]2x {}^{2} - 3x + 1 = 0[/tex]

[tex]a = 2 \: \: \: \: b = - 3 \: \: \: c = 1[/tex]

[tex]delta = b {}^{2} - 4ac[/tex]

[tex]delta = ( - 3) {}^{2} - 4.2.1 = 9 - 8 = 1[/tex]

[tex] \sqrt{1} = 1[/tex]

[tex]x1 = \frac{ - ( - 3) + 1}{2.2} = \frac{3 + 1}{4} = \frac{4}{4} = 1[/tex]

[tex]x2 = \frac{ - ( - 3) - 1}{2.2} = \frac{3 - 1}{4} = \frac{2}{4} = \frac{1}{2} [/tex]